Women who do: female disciples in the gospels - Carey, Holly J. (Eerdmans, 2023)
Intro -- Title Page -- Copyright -- Dedication -- Contents -- Preface -- Introduction: Female Discipleship in the Gospels -- 1. A Woman's World in the First Century -- 2. Female Discipleship in the Gospel of Mark -- 3. Female Discipleship in the Gospel of Matthew -- 4. Female Discipleship in the Gospel of Luke -- 5. Female Discipleship in the Acts of the Apostles -- 6. Female Discipleship in the Gospel of John -- Conclusion: Women in the Gospels as Models of Discipleship -- Bibliography.